The Adversity Quotient Of Pesantren Students: The Effects Of Academic Stress, Emotional Intelligence, Academic Self-Concept and Social Supports - Rena Latifa; Lia Amaliyatul Islami (Program Studi Psikologi Islam, Fakultas Psikologi, Universitas Islam Negeri Raden Fatah Palembang, 2020)
The life of students at Pesantren is usually filled with a dense series of activities, requiring high discipline, accompanied by demands to master knowledge and the implementation of religious values. Such activities are special features of Pesantren education which must be carried out by students every day so that such activities become challenges that must be faced by students. The foregoing sometimes makes students have difficulties in learning processes at Pesantren. The difficulties range from academic pressure to the process of making adjustments to Pesantren environment. Adversity quotient is considered an important concept in students’ mental development. Students’ success and failure in education can be determined by the extent of adversity quotient. Hence, this study aimed to examine the predictors of students’ adversity quotient formation, namely: academic stress, emotional intelligence, academic self-concept, and social supports. Respondents in this study were 268 students of grade VII, VIII, and IX at Pesantren Daar El-Qolam. Sampling deployed a non-probability sampling method using a purposive sampling technique. The validity of measuring instruments was tested by Confirmatory Factor Analysis (CFA). Data analysis used multiple regression analysis. The results of this study indicated that academic stress, emotional intelligence, academic self-concept, and social supports had significant joint effects on adversity quotient as high as 41.0%, the rest was influenced by errors or other factors which were not examined in this study.